Lack of association between RANTES-28, SDF-1 gene polymorphisms and systemic lupus erythematosus in the Malaysian population - Lian, L.H.; Kee, B.P.; Ng, H.L.; Chua, K.H. (2011)
Regulated on activation, normal T-cell expressed and secreted (RANTES) and stromal cell-derived factor 1 (SDF-1) are members of the CC- and CXC-chemokine families, respectively. Both genes have been postulated to be involved in the pathogenesis of systemic lupus erythematosus (SLE). We analyzed position 28 of the RANTES gene promoter region, as well as the SNP observed in the 3' UTR of the SDF-1 gene at position 801, in 130 patients presenting SLE at the Malaya University Medical Centre. Screening of 130 healthy volunteer controls using RFLP was also performed. RANTES-28 polymorphism analysis showed no significant (P = 0.3520) relationship, even though homozygous C/C was more frequent in SLE patients (OR = 1.4183) and heterozygous C/G was more frequent in healthy controls (OR = 0.7051). There were no significant (P = 0.2650) associations between A/A (OR = 0.783), G/G (OR = 1.5914) and G/A (OR = 0.8289) genotypes in the SDF-1 gene polymorphism with SLE. We conclude that there is no significant association of RANTES-28 and SDF-1 gene polymorphisms and occurrence of SLE in Malaysia.